Florística e ecologia de epífitas vasculares em um fragmento de floresta de restinga, Ubatuba, SP, Brasil - Mania, Luiz Felipe [UNESP] (2010)
Vascular epiphytism plays a significant role in the diversity of tropical forests and it also provides food resources and microhabitats for specialized fauna of the canopy. We present the epiphyte community of a “restinga” high forest on the coastal plain of Fazenda Beach, Picinguaba Sector of Serra do Mar State Park, located in northern Ubatuba municipality/São Paulo. The vascular epiphyte species were sampled monthly for a period of one year, resulting in 64 species, 37 genera and 12 families identified. Orchidaceae, Bromeliaceae, Polypodiaceae and Araceae were the most representative families, totaling 75% of all species. The life form “true epiphytes” was the richest in species (73.4%), with a monocot majority (55.3%). Next in order are the “facultative” group (14.1%), exclusively Bromeliaceae and Lomariopsidaceae, the “secondary” group (6.3%) and “primary” (3.1%) hemiepiphytes, exclusively Araceae, and the “accidental” and “preferred” epiphytes (1.6% each).